The Effect of Hypnotherapy on the Reduction of Blood Glucose Levels in Diabetes Mellitus Type-2 - Hasymi, Yusran; Suwanto, . (KnE Life Sciences, 2021)
Diabetes mellitus is a group of metabolic diseases characterized by hyperglycemia, which occurs due to abnormalities in insulin secretion, insulin action, or both. Most cases of diabetes mellitus are diabetes mellitus type-2. The purpose of this study was to determine the effect of hypnotherapy on reducing blood glucose levels in patients with diabetes mellitus type-2. The research used a quasi-experimental design with a non-equivalent control group design. Purposive sampling was used, and 30 respondents selected. The instrument in this study was a single stick tool. The intervention group was given standard therapy treatment in the form of bio-energy therapy and hypnotherapy, while the control group was only given standard therapy treatment in the form of bio-energy therapy. Univariate analysis of the results indicates that the average blood glucose level before treatment was 234.67 mg/dl and after treatment was 194.67 mg / dl. Bivariate analysis based on the results of the Wilcoxon Signed Ranks Test obtained a p-value of 0.002 (p-value <0.05). This means that hypnotherapy reduced blood glucose levels in diabetes mellitus type-2 sufferers. This study recommends the nursing profession apply hypnotherapy as an alternative or non-pharmacological complementary therapy that can be used to reduce blood glucose levels in people with diabetes mellitus type 2. Keywords: Hypnotherapy, diabetes mellitus type 2, blood glucose levels